Revascularisation of left hand after 33 hours of warm ischemia: a case report - Gharwade, Chandrakant R.; Alegaonkar, Umesh; Jawade, Pranav G.; Gharwade, Shweta C. (International Surgery Journal, 2016)
‘Revascularisation’ or ‘replantation’ is a limb saving procedure. In case of severe limb injury compromising its vascularity, before considering amputation, one should always consider these surgical procedures after thoroughly assessing the status of the patients injury and his hemodynamic status. Delayed revascularisation has proven successful in cases and there are substantial evidences based on some case studies published recently. There are very few reports and case studies documented on successful salvage of upper limb /forearm traumatic vascular injuries after considerable delay in revascularisation / replantation. Here we present a case of delayed revascularisation of left hand after 33 hours of warm ischemia which turned out to be a successful surgery without any dreadful complication and consequences in a year’s follow-up. We believe and recommend that efforts must be made by every well-equipped health care system in salvaging the limb by revascularisation technique. We also want to mention that delayed revascularisation can be done successfully with constant monitoring of limb and patients hemodynamic status to rule out reperfusion injury and septicaemia. We recommend, one should always consider revascularisation/ Replantation as an option before planning amputation which can be debilitating for the patient.